An Alternative to the Liberal World Order: China, BRICS, and Middle East Diplomacy - Lee, Brice Tseen Fu; Kornphetcharat, Kotchaphop; Sims, Juan Pablo (Journal Of Middle East and Islamic Studies, 2025)
This paper explores how China and BRICS are emerging as strategic alternatives to the liberal international order, particularly in the realm of diplomacy and mediation for periphery states in the Middle East. Drawing on a realist theoretical framework, the study argues that these platforms offer pragmatic, interest-based avenues for engagement that contrast sharply with the conditionalities and normative expectations of Western-led institutions. Through case studies such as China’s mediation in the Iran–Saudi Arabia normalization and the expansion of BRICS+ to include Middle Eastern actors, the paper demonstrates how sovereignty, non-interference, and multipolarity have become central organizing principles for a new diplomatic architecture. For periphery states traditionally excluded or constrained by the liberal order, BRICS and China provide critical tools to bargain, hedge, and enhance agency in an increasingly fragmented world.